2020
DOI: 10.1155/2020/8237101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Community-Led Total Sanitation and Hygiene on Prevalence of Diarrheal Disease and Associated Factors among Under-Five Children: A Comparative Cross-Sectional Study in Selected Woredas of Gamo Gofa Zone, Southern Ethiopia

Abstract: Background. Diarrheal diseases are still one of the major causes of morbidity in under-five children in sub-Saharan Africa. In Ethiopia, diarrhea is responsible for 9% of all deaths and is the major cause of under-five mortality. Objective. To assess the impact of community-led total sanitation and hygiene on the prevalence of diarrheal disease and factors associated among under-five children in Gamo Gofa Zone. Methods. Community-based comparative cross-sectional study design was used to compare the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
4
2
0
1
Order By: Relevance
“…Children aged 36-59 months were 3.17 times more affected by diarrhea than children age less than 12 months. This is consistent with other studies conducted in Amhara region, Gamo Gofa Zone, Sidama Zone, Ethiopia [ 4 , 7 , 29 ], Tanzania [ 31 ], and northern Uganda [ 14 ]. A higher percentage of diarrhea cases have occurred among the highest birth order.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Children aged 36-59 months were 3.17 times more affected by diarrhea than children age less than 12 months. This is consistent with other studies conducted in Amhara region, Gamo Gofa Zone, Sidama Zone, Ethiopia [ 4 , 7 , 29 ], Tanzania [ 31 ], and northern Uganda [ 14 ]. A higher percentage of diarrhea cases have occurred among the highest birth order.…”
Section: Discussionsupporting
confidence: 92%
“…Children who had ever been breastfed had less likely to experience diarrhea as compared to children who had never breasted. This finding had conformity with a study done in Gamo Gofa Zone, Southern Ethiopia [ 29 ], Bahir Dar city, Northwest, Ethiopia [ 5 ], Medebay Zana district, northwest Ethiopia [ 13 ], and Ethiopia [ 32 ], which showed that children who were partially or not breastfed had a high risk of diarrhea death than exclusively breastfed children. This is because breastfeeding helps to protect child health by preventing contracting contagious diseases including diarrhea.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…r = number of positive variables in the balance V s = number of negative variables in the balance V g m (−) = geometric mean of variables However, to illustrate the behavior of the models in the transformed data, a type of balance is carried out, consistent with the usual form of analysis in the WASH sector. For example, global monitoring is based on the classification of access to improved and unimproved water and sanitation services, which are subsequently subdivided into service categories (WHO/UNICEF, 2017; Turman-Bryant et al, 2018); likewise, both inequalities in access to water and sanitation (Yang et al, 2013;Bain et al, 2014;Anthonj et al, 2020b;Chitonge et al, 2020) as well as studies of access to WASH and its relation to health (Prüss-Ustün et al, 2014;Freeman et al, 2017;Ashole Alto et al, 2020;Hasan and Alam, 2020;Patel et al, 2020) imply in one way or another the classification of improved and unimproved services. Therefore, the order of the balances (Egozcue and Pawlowsky-Glahn, 2005) is defined under this criterion (see Fig.…”
Section: Step I Preparation Of Compositional Data (Coda)mentioning
confidence: 99%